2017
DOI: 10.3390/f8110460
|View full text |Cite
|
Sign up to set email alerts
|

Soil Degradation and the Decline of Available Nitrogen and Phosphorus in Soils of the Main Forest Types in the Qinling Mountains of China

Abstract: Soil degradation has been reported worldwide. To better understand this degradation, we selected Pinus armandii and Quercus aliena var. acuteserrata forests, and a mixed forest of Q. aliena var. acuteserrata and P. armandii in the Qinling Mountains in China for our permanent plots and conducted three investigations over a 20-year period. We determined the amounts of available nitrogen (N) and phosphorus (P) in the soil to track the trajectory of soil quality and compared these with stand characteristics, topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Some studies demonstrated that higher AF in soils could promote plant growth (Zhao et al 2009 ; Xiao et al 2012 ). The study of Zheng et al ( 2017 ) showed that the pine-dominated forests had the highest content of phosphorus in soil, while the mixed forests and oak-dominated forests had slightly lower content P. This was confirmed by this study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Some studies demonstrated that higher AF in soils could promote plant growth (Zhao et al 2009 ; Xiao et al 2012 ). The study of Zheng et al ( 2017 ) showed that the pine-dominated forests had the highest content of phosphorus in soil, while the mixed forests and oak-dominated forests had slightly lower content P. This was confirmed by this study.…”
Section: Discussionsupporting
confidence: 88%
“…This may result in a significant decrease in soil phosphorus (Vitousek et al 2010 ). The study on Zheng et al ( 2017 ) showed that temperature is the most critical factor controlling the soil nitrogen, and species composition is the main factor regulating the soil available phosphorus.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, low values in N were linked to plots with species composition resembling cloud forests whose biodiversity is one of the highest among the mountain forest in Mexico (Gual-Díaz & Rend on-Correa, 2014). Moreover, the elevation gradient in this study is related to low temperatures, which is an important factor in the regulation of N and P (Zheng et al, 2017); steep slopes also allow deep soil accumulation, which increases bedrock weathering to preserve mineral-derived nutrients, such as Ca, Mg, K, and P. High values of precipitation and humidity are also critical factors affecting P distribution in soil, even more limiting that N (which is deposited largely from the atmosphere); therefore, its mineralization in organic form accounts for its supply to plants (Shiau et al, 2018). The process explained above must be taking place in the study area as litter was a significant variable explaining species composition in the Quercus-dominated forest.…”
Section: Sizesmentioning
confidence: 85%
“…Analysis data indicated that the AN showed an increasing trend with the chronosequence, while the AP and AK showed an opposite trend. Researchers proposed that the concentrations of soil available nutrients (i.e., AN, AP, and AK) were species-dependent, which could be explained by the "complementary" or "mass" effects related to plant diversity in forest ecosystems (Zheng et al, 2017;Liu et al, 2021). Han et al (2021) demonstrated that the content of AK showed a positive correlation with BD.…”
Section: Changes In Soil Physico-chemical Properties During Forest Re...mentioning
confidence: 99%